PEMBERDAYAAN MASYARAKAT MELALUI BUDIDAYA MAGGOT BLACK SOLDIER FLY SEBAGAI SOLUSI PENGELOLAAN LIMBAH ORGANIK DAN PENINGKATAN EKONOMI DI DESA LABORATORIUM TERPADU PUDAK - Weni Wilia; Herni Dwinta Pebrianti; Yulia Alia; Agus Kurniawan Mastur; Dedy Antony; Yusfaneti (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Pudak Village, Kumpeh Ulu District, is approximately 19 km from the Pinang Masak Campus of Jambi University and is a rice production center covering approximately 180 hectares. To support sustainable agriculture, Black Soldier Fly (BSF) maggot cultivation is a potential innovation because it can decompose household and agricultural organic waste, while simultaneously producing highly nutritious animal feed and organic fertilizer. The main obstacle faced by farmers is a lack of knowledge about maggot cultivation techniques and their use in integrated farming systems. This activity aims to improve farmers' understanding and skills through outreach and field practice, covering maggot cultivation, waste utilization as a medium, and crop application. This program is expected to reduce dependence on chemical fertilizers, increase rice productivity, and sustainably preserve the environment